Causal relationships between body mass index, smoking and lung cancer: Univariable and multivariable Mendelian randomization. Issue 5 (23rd September 2020) - Zhou, Wen; Liu, Geoffrey; Hung, Rayjean J.; Haycock, Philip C.; Aldrich, Melinda C.; Andrew, Angeline S.; Arnold, Susanne M.; Bickeböller, Heike; Bojesen, Stig E.; Brennan, Paul; Brunnström, Hans; Melander, Olle; et al.
Abstract: At the time of cancer diagnosis, body mass index (BMI) is inversely correlated with lung cancer risk, which may reflect reverse causality and confounding due to smoking behavior. We used two‐sample univariable and multivariable Mendelian randomization (MR) to estimate causal relationships of BMI and smoking behaviors on lung cancer and histological subtypes based on an aggregated genome‐wide association studies (GWASs) analysis of lung cancer in 29 266 cases and 56 450 controls. We observed a positive causal effect for high BMI on occurrence of small‐cell lung cancer (odds ratio (OR) = 1.60, 95% confidence interval (CI) = 1.24‐2.06, P = 2.70 × 10 −4 ). After adjustment of smoking behaviors using multivariable Mendelian randomization (MVMR), a direct causal effect on small cell lung cancer (ORMVMR = 1.28, 95% CI = 1.06‐1.55, P MVMR = .011), and an inverse effect on lung adenocarcinoma (ORMVMR = 0.86, 95% CI = 0.77‐0.96, P MVMR = .008) were observed. A weak increased risk of lung squamous cell carcinoma was observed for higher BMI in univariable Mendelian randomization (UVMR) analysis (ORUVMR = 1.19, 95% CI = 1.01‐1.40, P UVMR = .036), but this effect disappeared after adjustment of smoking (ORMVMR = 1.02, 95% CI = 0.90‐1.16, P MVMR = .746). These results highlight the histology‐specific impact of BMI on lung carcinogenesis and imply mediator role of smoking behaviors in the association between BMI and lung cancer. Abstract : What's new? Lung cancer risk appears to be inversely correlated with BMI, which could be due to a variety of factors. Here, the authors used Mendelian randomization (MR) to look for a causal effect of BMI on lung cancer. MR uses genetic variants as instrumental variables, and avoids the effects of confounding factors. However, linkage disequilibrium with causal variants may interfere with the results. After adjustment for smoking, the authors found a direct causal effect of BMI on small cell lung cancer, and an inverse effect on lung adenocarcinoma. These results highlight that the effect of BMI varies significantly depending on histology.